Pathogenesis of Bacterial Infections in Animals 2004
DOI: 10.1002/9780470344903.ch10
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelothrix Rhusiopathiae

Abstract: Types of E. coli Implicated in Disease Enterotoxigenic E. coli (ETEC) Pathogenesis Shiga Toxin-Producing Escherichia coli (STEC) Enteropathogenic E. coli (EPEC) Pathogenesis Extraintestinal E. coli (ExPEC) Immunity Concluding Remarks 17 Actinobacillus J. I. MacInnes and J. T. Bossé Actinobacillus pleuropneumoniae Actinobacillus suis Actinobacillus equuli Actinobacillus lignieresii Conclusions and Future Prospects 18 Haemophilus T. J. Inzana and L. Corbeil Characteristics Habitat and Transmission Haemophilus so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
9

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 24 publications
0
1
0
9
Order By: Relevance
“…These phospholipases may allow the organism to escape from phagosomes into the cytoplasm by disrupting the phagosomal membrane (43). In fact, electron microscopic observation revealed that the organism multiplies predominantly within the cytoplasm of macrophages at the inoculation sites of mice (46), suggesting that the cytoplasm serves as a privileged in vivo niche for E. rhusiopathiae, which allows the organism to circumvent host immune responses. Antioxidant enzymes and phospholipases could also modulate immunological cell-signaling pathways (2,44).…”
Section: Resultsmentioning
confidence: 99%
“…These phospholipases may allow the organism to escape from phagosomes into the cytoplasm by disrupting the phagosomal membrane (43). In fact, electron microscopic observation revealed that the organism multiplies predominantly within the cytoplasm of macrophages at the inoculation sites of mice (46), suggesting that the cytoplasm serves as a privileged in vivo niche for E. rhusiopathiae, which allows the organism to circumvent host immune responses. Antioxidant enzymes and phospholipases could also modulate immunological cell-signaling pathways (2,44).…”
Section: Resultsmentioning
confidence: 99%
“…Esta proteína possui estrutura e seqüência de aminoácidos na região C-terminal muito similares às das proteínas de ligação à colina do Streptococcus pneumoniae, uma das quais, apresenta função específica de adesina. No entanto, esta função da spaA na espécie E. rhusiopathiae ainda precisa ser elucidada (SHIMOJI, 2004). To e Nagai (2007), investigando a seqüência genética da proteína spaA, verificaram que os tamanhos da fase aberta de leitura (ORF) do gene spa variavam em comprimento conforme o sorotipo da cepa de E. rhusiopathiae.…”
Section: Fatores De Virulênciaunclassified
“…Dessa maneira, as proteínas spa foram divididas em três espécies moleculares designadas de spaA (abrangendo os sorotipos 1a, 1b, 2, 5, 8, 9, 12, 15, 16, 17 e N), spaB (sorotipos 4, 6, 11, 19 e 21) A neuroaminidase (sialidase) libera os resíduos terminais do ácido siálico de glicoproteínas, glicolipídeos e oligossacarídeos expressos pelas células hospedeiras (SHIMOJI, 2004). Nakato, Shinomiya, Mikawa (1986a) observaram uma distribuição in vivo da invasão bacteriana concomitante à perda de ácido siálico dos sítios das regiões arteriais, assim como uma adesão in vitro de E.…”
Section: Fatores De Virulênciaunclassified
See 2 more Smart Citations